A case series of CBT‐T in routine clinical practice. Issue 8 (17th June 2021) - Rose, Charlotte; Bakopoulou, Ioanna; Novak, Tamas
Abstract: Objective: CBT‐T is a relatively new, brief cognitive behavioral therapy eating disorder treatment for non‐underweight patients. This study evaluates CBT‐T independently from the team that developed the protocol, and examines the relationship between eating disorder duration and CBT‐T effectiveness. Method: A case series design was used, comprising N = 40 adults with bulimia or atypical anorexia type eating disorders. CBT‐T was delivered by CBT therapists in a specialist outpatient service. Mixed model analysis examined the interactions between eating disorder duration and change to eating disorder psychopathology and secondary impairment from pre‐post treatment. Abstinence, good outcome, and remission rates were also provided. Results: Intervention effect sizes were large. Treatment completers reported abstinence from binge eating and purging over the final 28‐days, and 7‐days of treatment at 30.1%, and 73.1%, respectively; 76.9% reported good outcome; and 23.1% reported remission. No relationship between eating disorder duration and treatment effectiveness was found. Discussion: These findings build on existing evidence supporting provision of CBT‐T in routine clinical practice, for patients with eating disorders of any duration. Replication, extension, and RCT will strengthen comparability with other evidence‐based approaches.